Regulation of mental states boaters qualifications during competition - Родина [Yuliya Rodina], Юлія Дмитрівна (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">The<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">article<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">studies<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">monitoring<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">of<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">mental<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">states<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">that<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">are<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">experiencing<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">a<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">competitive<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">yachtsman<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">week.<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">The<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">effect<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">of<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">the<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">program<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">self-regulation<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">on<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">the<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">psyche<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">of<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">skilled<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">yachtsman<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">of<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">the<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">Olympic<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">team<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">of<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">Ukraine<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">are<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">researched.<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">Compares<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">the<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">results<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">of<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">boaters<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">who<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">used<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">the<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">program<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">of<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">self-regulation<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">during<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">the<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">passage<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">of<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">the<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">race<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">and<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">a<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">group<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">of<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">boaters<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">who<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">were<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">competitions<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">following<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">the<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">usual<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">program.<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">Screening<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">and<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">diagnostics<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">performed<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">by<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">the<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">method<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">gas<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">discharge<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">visualization.<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">The<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">conclusions<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">of<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">the<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">government<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">in<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">improving<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">performance<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">boaters<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">who<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">use<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">the<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">program<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">of<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">self-regulation<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">(mental<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">training),<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">and<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">a<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">statistically<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">significant<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">impact<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">of<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">this<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">program<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">on<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">the<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">psyche<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">of<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">the<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">athletes<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">that<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">can<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">help<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">improve<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">their<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: SimSun; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US">psychological<span style="font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: .5pt; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: HI;" lang="EN-US"> preparedness. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->